Tracheal Intubation through the I-gel for Emergency Cesarean Section in a Patient with Multidrug Hypersensitivity: A New Technique - Kartika Balaji Samala; Yuri Uchiyama; Yasuyuki Tokinaga; Yukitoshi Niiyama; Soshi Iwasaki; Michiaki Yamakage (Case Reports in Anesthesiology)
31-year-old female with hypersensitivity to local anesthetics and neuromuscular blocking agents presented for emergency Cesarean section. We successfully performed I-gel-assisted tracheal intubation without using neuromuscular blockers. We believe this method would be helpful in selected situations.